2019
DOI: 10.1038/s41598-018-38284-x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Effort cost Decision-making in Healthy Individuals with Subclinical Psychotic Symptoms

Abstract: The value people attribute to rewards is influenced both by the time and the effort required to obtain them. Impairments in these computations are described in patients with schizophrenia and appear associated with negative symptom severity. This study investigated whether deficits in temporal and effort cost computations can be observed in individuals with subclinical psychotic symptoms (PS) to determine if this dysfunction is already present in a potentially pre-psychotic period. Sixty participants, divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…A range of studies have found that individuals with psychotic disorders or schizophrenia have effort-related impairments (Barch et al, 2014;Whitton et al, 2015) and that there is an association between the degree of negative symptoms and these impairments (Bergé et al, 2018). In healthy populations similar findings have been reported for negative symptom-like phenomena (Stefanis et al, 2002;Terenzi et al, 2019).…”
Section: Motivation Vigor and Effort-based Decision Making In Psychmentioning
confidence: 52%
“…A range of studies have found that individuals with psychotic disorders or schizophrenia have effort-related impairments (Barch et al, 2014;Whitton et al, 2015) and that there is an association between the degree of negative symptoms and these impairments (Bergé et al, 2018). In healthy populations similar findings have been reported for negative symptom-like phenomena (Stefanis et al, 2002;Terenzi et al, 2019).…”
Section: Motivation Vigor and Effort-based Decision Making In Psychmentioning
confidence: 52%
“…Overall, these findings suggest that not all subdimensions of PLEs are associated with conspiratorial beliefs and that both the positive (possibly through cognitive processes such as the jump to conclusion bias) and negative (reduced motivation) dimensions of PLEs may contribute to believing in conspiracy theories. In line with these findings, a study by Ståhl and colleagues (2018) proposed that skepticism towards conspiratorial beliefs requires sufficient cognitive and motivational abilities, which are both altered in individuals with high levels of PLEs 9,28,29 .…”
Section: Discussionmentioning
confidence: 90%
“…The Community Assessment of Psychic Experience (CAPE) is a 42-item questionnaire that measures self-reported subclinical psychotic symptoms in the general population based on three dimensions: positive symptoms, negative symptoms, and depression 44,45 . Several studies have shown that the CAPE can be a screening tool to identify people who might be at risk for psychosis 9,10,46 .…”
Section: Psychotic-like Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A better understanding of specific impairments in effort-based decision-making will ultimately lead to better strategies for treating disabling amotivation. As clinical amotivation and reduced willingness to exert effort in behavioral tasks are also observed in first episode psychosis and clinical high risk for psychosis [77][78][79] neurobehavioral biomarkers of amotivation may also provide targets for early detection and intervention.…”
Section: Discussionmentioning
confidence: 99%